(untitled) (Symposium on Natural and Applied Sciences, 2026)
This thesis investigates the influence of high-temperature thermal treatment on the structural state of n-type silicon monocrystals using X-ray diffraction analysis. Particular attention is focused on the (111)Si diffraction peak, which is the dominant reflection for the investigated n-Si samples. The XRD patterns show that the initial n-Si monocrystal exhibits a sharp and intense (111)Si peak near 2θ ≈ 28.5°, indicating a highly oriented crystalline structure. After annealing at 1300 °C, the intensity of the (111)Si reflection decreases significantly, while the peak position slightly shifts and the full width at half maximum changes from 0.144° to 0.134°. These changes indicate that thermal treatment causes structural reorganization in the silicon lattice, including redistribution of impurity atoms, partial relaxation of internal stresses, and modification of defect-related microstrain. The decrease in peak intensity suggests a reduction in the coherently diffracting volume, whereas the narrowing of the diffraction peak may be associated with partial ordering or enlargement of coherent scattering regions. The obtained results confirm that high-temperature annealing is an important technological factor influencing the crystallographic perfection and microstructural state of phosphorus-doped n-type silicon monocrystals.